Pelatihan Penggunaan Sistem Interaktif sebagai Media Alternatif Penyuluhan Narkoba di Kabupaten Pangandaran - Retnowati, Yulia; Muhammad, Raditya; Ardimansyah, Mochamad Iqbal; Hendriyana, Hendriyana; Septiana, Asyifa Imanda; Anggraini, Dian; Syawanodya, Indira (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2025)
The younger generation is particularly susceptible to the dangers of drug abuse due to the potential long-term consequences associated with narcotics use. Consequently, they often find themselves in the crosshairs of drug trafficking syndicates seeking financial gain. In response to this issue, the government, working in conjunction with the National Narcotics Agency (BNN), has introduced the Program for Prevention, Eradication, Abuse, and Illicit Trafficking of Drug Precursors (P4GNPN) as a strategic measure to combat drug trafficking. Aligned with the broader anti-narcotics movement in Indonesia, our implementation team has launched a training program aimed at harnessing the power of interactive systems to serve as an educational tool on drug-related matters. The primary recipients of this program are teachers who are active members of the Indonesian Teachers Association (PGRI) in Pangandaran Regency. The fundamental objective of employing this interactive system is to empower users with the capability to access drug information and counseling interactively and on a personal basis, regardless of their location or the time of day. The participants have been thoroughly trained in the proper use and effective utilization of this interactive system. According to the feedback obtained through the evaluation process, participants have expressed a clear understanding of the material, and the training has significantly boosted their motivation to carry out anti-drug movements. With the introduction of this community service initiative, we aspire to lend support to the government's and society's collective efforts in addressing the pressing issue of drug abuse among the younger generation.